PENINGKATAN MINAT BELAJAR DENGAN METODE PERMAINAN DALAM BELAJAR BAHASA MANDARIN - Ivana, Ivana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Mastery of foreign languages, especially Mandarin, is something that must be done by the younger generation, but Mandarin is very difficult to learn, even though educators have used flash card media and PowerPoint media, their use is too monotonous, so this still causes boredom for students. the students. The purpose of this study was to examine whether the game method combined with flash card media and PowerPoint slides could increase the learning interest of Methodist Charles Wesley students. The data analysis used is Miles & Huberman's data analysis. The results of this study are: (1) The game is not the most important in learning, but is a complementary method to increase students' interest in learning. (2) Educators must be creative in choosing games. And in the game method which is combined with flash card media and powerpoint slide media, it also has its own challenges, namely: educators must spend more time preparing materials and learning how to use these media more creatively.